Correction: Structural and photophysical characterization of mono- and binuclear Cu(i) complexes based on carbohydrazones: a combined experimental and computational study. Issue 20 (10th May 2016) - Gholivand, Khodayar; Farshadfar, Kaveh; Roe, S. Mark; Gholami, Akram; Esrafili, Mehdi D.
Abstract : Correction for 'Structural and photophysical characterization of mono- and binuclear Cu(i ) complexes based on carbohydrazones: a combined experimental and computational study' by Khodayar Gholivand et al., CrystEngComm, 2016, 18, 2873–2884.